Strategic aspects of digitalisation of administrative services (Economics and region, 2024)
The article focuses on the strategic aspects of digitalisation of administrative services and their impact on public administration. The introduction discusses the importance of integrating digital technologies into public services, which can increase the efficiency, transparency and accessibility of services for citizens. The main challenges faced by digitalisation include unequal access to technology, insufficient infrastructure in rural areas, and low levels of digital literacy. The objective of the study is to identify a strategy for implementing digital tools that will improve access to administrative services and integrate citizens into the digital ecosystem. The main results of the study show the importance of infrastructure and educational measures for the successful implementation of digitalisation. In Ukraine, the Diia platform is an important step in the modernisation of administrative services, but there are problems with Internet access, especially in rural areas, which limits the effectiveness of this platform. The study analysed existing models of digitalisation of administrative services in Ukraine and compared their effectiveness with international practices. The results of the study allowed us to identify the key factors influencing the success of digital transformations and develop recommendations for optimising the process of implementing electronic services. The study analysed current digital initiatives in the field of administrative services in Ukraine, in particular, the impact of the Diia platform on the availability and efficiency of services for citizens. Special attention is paid to infrastructure issues, such as insufficient access to high-speed Internet in rural areas, and their impact on the success of digitalisation. The study also covers cybersecurity and personal data protection, which are critical to public trust in electronic services. The collected data allows us to formulate recommendations for improving digital infrastructure and increasing the level of digital literacy among the population. The article concludes by focusing on the importance of a strategic approach to digitalisation, including the development of the legal and regulatory framework, ensuring cybersecurity and personal data protection, and increasing citizens' trust in electronic services. Successful digitalisation requires a comprehensive solution to technical, financial and social problems, which will allow building a service state that will meet the needs of citizens in the 21st century.
Keywords: administrative services; digitalisation; e-services; Diia; public administration; service state